Phylogeographic pattern suggests a general northeastward dispersal in the distribution of Machilus pauhoi in South China. - Qin Zhu (PLoS ONE, 2017)
Machilus pauhoi Kanehira is an important timber species in China. A provenance trial was recently set up to evaluate the growth performance of trees from different localities, with the aim of designing seed transfer guidelines. Here, we tested twelve nuclear microsatellite markers derived from other species of the Lauraceae family and investigated population genetic structure in M. pauhoi. Both the number of observed alleles per locus (Na) and the polymorphic information content (PIC) significantly decreased against the latitude, but showed an insignificant decrease against the longitude. Heterozygosity (Ho) and gene diversity (h) exhibited a weak correlation with geographic location. Private alleles were present in multiple populations, and a moderate level of population genetic differentiation was detected (Gst = 0.1691). The joint pattern of genetic diversity (Na, PIC, Ho, and h) suggests that general northeastward dispersal led to the current distribution of M. pauhoi. Significant but weak effects of isolation-by-distance (IBD) occurred, implicating the mountain ranges as the major barrier to gene flow. Both STRUCTURE and hierarchical clustering analyses showed three distinct groups of populations related to the physical connectivity among mountain ranges. A priority in designing genetic conservation should be given to the populations at the southwest side of the species' distribution. This conservation strategy can also be combined with the pattern of adaptive genetic variation from the provenance trial for comprehensive genetic resource management of native M. pauhoi.